GORK, a delayed outward rectifier expressed in guard cells of Arabidopsis thaliana, is a K(+)-selective, K(+)-sensing ion channel. - Ache, Peter; Becker, Dirk; Ivashikina, Natalya; Dietrich, Petra; Roelfsema, M. R. G.; Hedrich, Rainer (Febs Letters, 2000)
Here we report on the molecular identification, guard cell expression and functional characterization of AtGORK, an Arabidopsis thaliana guard cell outward rectifying K(+) channel. GORK represents a new member of the plant Shaker K(+) channel superfamily. When heterologously expressed in Xenopus oocytes the gene product of GORK mediated depolarization-activated K(+) currents. In agreement with the delayed outward rectifier in intact guard cells and protoplasts thereof, GORK is activated in a voltage- and potassium-dependent manner. Furthermore, the single channel conductance and regulation of GORK in response to pH changes resembles the biophysical properties of the guard cell delayed outward rectifier. Thus GORK very likely represents the molecular entity for depolarization-induced potassium release from guard cells.